Reconceptualizing Mathematics Teacher Education Through Human-Centered Metaphorical Thinking: A Reflective Cognition Design Model for Pre-Service Primary Teachers - Jusmawati Jusmawati; Satriawati Satriawati; Hafsyah Hafsyah; Rustiani S; Pratiwi Pujilestari Alam (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
This study addresses the persistent gap between lecturer-centered instruction and the underdeveloped mathematical reflective thinking of pre-service elementary teachers by designing, validating, and testing an instructional model termed METRIS (Metaphorical Thinking Reflective Instructional Scaffold). Employing a research-and-development design that namely analysis, design, prototyping, evaluation, and implementation for dissemination, the study engaged pre-service elementary teachers across three teacher-education institutions in South Sulawesi, Indonesia. The model attained a mean validity score of 3.61 (very valid), an implementation-agreement rate of 98 percent, and an effectiveness gain rising from 66 percent to 75 percent across trials, with the experimental group significantly outperforming the control group, t (68) = 6.37, p < .001. These findings indicate that mediating abstract mathematical structures through learner-generated metaphors operationalizes constructivist and cognitivist learning principles into a teachable, assessable classroom syntax. The study contributes an empirically validated, transferable pedagogical model to the underexplored intersection of metaphor-based instruction and reflective cognition in teacher education, offering both a theoretical bridge between metaphor theory and reflective-judgment theory and a practical scaffold that teacher-education programs elsewhere can adapt, trial, and extend.